1985
DOI: 10.2307/1590465
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo Characterization of Avian Escherichia coli. III. Immunization

Abstract: Broiler breeder hens were vaccinated once at 20 weeks or twice at 20 and 25 weeks of age with a formalin-inactivated oil-emulsion Escherichia coli bacterin composed of serogroups O2, O78, and O35. Serological responses as assessed by microagglutination documented an increase in serotype-specific antibody in vaccinated birds. Challenge of progeny from vaccinates and nonvaccinates with homologous E. coli demonstrated that maternally derived antibody could protect against mortality and/or lesions for as long as 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 5 publications
3
26
0
Order By: Relevance
“…Mutants of E. coli not only produce colonies appearing 'rough' on solid media but also become non-typable as standard serological methods of serotyping do not allow the determination of their specific antigenicity. Such non-typable strains have on many occasions been isolated from clinical cases of avian colisepticaemia (Rosenberger et al, 1984) and studies of their pathogenic properties showed that some of them are highly pathogenic to day-old broiler chicks (Rosenberger et al, 1985). In this regard results presented here confirm earlier reports.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Mutants of E. coli not only produce colonies appearing 'rough' on solid media but also become non-typable as standard serological methods of serotyping do not allow the determination of their specific antigenicity. Such non-typable strains have on many occasions been isolated from clinical cases of avian colisepticaemia (Rosenberger et al, 1984) and studies of their pathogenic properties showed that some of them are highly pathogenic to day-old broiler chicks (Rosenberger et al, 1985). In this regard results presented here confirm earlier reports.…”
Section: Discussionsupporting
confidence: 90%
“…Rosenberger et al (1984) reported that 16 out of 95 E. coli isolates were nontypable and highly or moderately pathogenic to 1-day-old broiler chicks. Nakamura et al (1982), testing fluctuation of drug-resistant E. coli strains, has isolated some non-typable forms from the fluff of hatchers and from day-old chicks.…”
Section: Introductionmentioning
confidence: 99%
“…For embryo lethality studies, three additional APEC isolates were used: APEC V1 (O nontypeable) and APEC V2 and V7 (both O2). For 1-day-old chick studies, three strains previously characterized as being of high, intermediate, and low lethality towards birds were used (53). All isolates were serogrouped through the E. coli Reference Center (Pennsylvania State University, University Park, PA) and were screened for traits associated with APEC and UPEC virulence, using the techniques described below.…”
Section: Methodsmentioning
confidence: 99%
“…Of these, 556 isolates were previously characterized for the presence of a subset of the genes included in this study (37). Also included among the 794 APEC isolates were 124 strains that were previously assigned to low-, intermediate-, or high-pathogenicity groups based on lesions and mortalities observed in experimentally infected chicks (6,39,40). Isolates were serogrouped by the E. coli Reference Center at Pennsylvania State University, University Park.…”
Section: Bacterial Strainsmentioning
confidence: 99%